Use of the image exchange communication system for communicative development in Autism (Research, Society and Development, 2020)
The main objective is to evaluate the use of the PEC'S system, being an alternative communication, in the treatment of autistic children who do not verbalize. This is bibliographic, explanatory and descriptive research. It presents itself with a subjective character of the analyzed object, in order to seek to understand its particularities, as a way of understanding how the PECS system is used, as a way of understanding the lexical repertoire of each individual. The treatment symbolizes one of the most effective therapeutic forms in autistic people who do not verbalize, however, its duration is indeterminate, and there may be individual variations, due to this, the treatment of cases must be individualized and singular. It was observed that the use of PECS, as a therapeutic method, favored the treatment of children with ASD, due to being a promoter of verbal communication, in which they present speech difficulties, despite being an individual teaching strategy.